Bioactivity and Volatile Profiling of Azadirachta indica Leaves for the Management of Maize Weevil, Sitophilus zeamais (Motsch.) Infestations - Perera, A.G.W.U.; Karunaratne, M.M.S.C.; Chinthaka, S.D.M. (Journal of Tropical Forestry and Environment, 2018)
Neem (Azadirachta indica A. juss), is known to possess a wide range of pharmacological properties and is thus commercially exploitable. Apart from its medicinal potential, a considerable progress has been achieved regarding biological potential and chemical composition of the leaves which is an ever-increasing interest to the scientific community. During this study, biological phenomena and secondary metabolite composition of A. indica leaves were examined in the management of Sitophilus zeamais on stored maize. Insecticidal and repellent potential of A. indica leaf powders were evaluated in both contact and fumigant forms. Phytochemical screening of 11 phyto constituents was performed following the standard procedures for n-hexane, dichloromethane, ethyl acetate, methanol and aqueous leaf extracts. Volatile profile of A. indica leaves was characterized by employing headspace-solid-phase micro extraction coupled with gas chromatography-mass spectrometry (HS-SPME/GC-MS). Over 60% weevil repellency was recorded at doses above 23.33%, whereas 100% and 67% contact and fumigation mortalities were observed respectively, 9 days after treatment at the dose of 33.33% and the respected LD50 values were 1.56 g and 4.48 g. Thirty two volatile compounds were identified in three distinct chemical classes (Monoterpenoid, sesquiterpenoid and purine nucleosides). γ-Elemene (24.06%), 3,7 (11)-eudesmadiene (6.83%), caryophyllene (6.40%), and 10s,11s-himachala-3(12),4-diene (6.36%) were the major constituents of neem leaf volatiles, followed by other compounds present in less than 4% which might be responsible for varied biological activities observed. Thus the odour impact of the bioassayguided study clearly implies that A. indica leaves can be harnessed against S. zeamais infestations. Keywords: Azadirachta indica, Sitophilus zeamais, headspace-solid-phase micro-extraction, insecticidal activity, repellency